2019
DOI: 10.1073/pnas.1814647116
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of bed bug infestations and control under disclosure policies

Abstract: Bed bugs have reemerged in the United States and worldwide over recent decades, presenting a major challenge to both public health practitioners and housing authorities. A number of municipalities have proposed or initiated policies to stem the bed bug epidemic, but little guidance is available to evaluate them. One contentious policy is disclosure, whereby landlords are obligated to notify potential tenants of current or prior bed bug infestations. Aimed to protect tenants from leasing an infested rental unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The study by Xie et al (19) is not without important caveats. For example, after relaxing the assumption that populations mixed randomly, they found that the costs and burdens became concentrated such that little overall benefit was realized.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…The study by Xie et al (19) is not without important caveats. For example, after relaxing the assumption that populations mixed randomly, they found that the costs and burdens became concentrated such that little overall benefit was realized.…”
mentioning
confidence: 90%
“…Their study demonstrates-using a mathematical model-that mandatory disclosures of bed bug infestations by landlords can lower economic costs and reduce the overall burden of bed bugs in a relatively short amount of time. The paper by Xie et al (19) sheds light on the significant epidemiological and economical consequences of bed bug infestation and opens many new avenues for future research.…”
mentioning
confidence: 99%
See 3 more Smart Citations